A Study on Climatic Subdivisions for the Viticulture in China - HUANG Shou-bo; CHEN Zhi-yin; SHEN Chao-dong; MCINTYRE G N; BRIDGMAN H A (浙江大学学报. 农业与生命科学版, 2000)
Grapes are one of the main fruit crops in China. In 1997, the annual production of grapes in the country was >2.03 million ton. This paper describes the geographic distribution and climatic subdivisions of viticulture in China. Eight agroclimatic regions were identified for climatic suitability of viticulture in China. To avoid or reduce the loss of meteorological hazards to viticulture, agroclimatic regions which most suitable (Ⅰ), suitable (Ⅱ. Ⅲ) or less suitable (Ⅳ, Ⅴ) should be chosen to cultivate grapevines species.